Predictability in securities price formation: Differences between developed and emerging markets - Silvio John Camilleri; Semiramis Vassallo; Ye Bai (Journal of Capital Markets Studies (JCMS), 2020)
Purpose This paper examines whether there are differences in the nature of the price discovery process across established versus emerging stock markets using a twenty-country sample. Design/methodology/approach The authors analyse security returns for traces of predictability or non-randomness using variance ratio tests, Granger-Causality models and runs tests. Findings The findings pinpoint at predictabilities which seem inconsistent with market efficiency, and they suggest that the inherent cause of predictability differs across groups. Research limitations/implications The authors present empirical evidence which may be used to attain a deeper understanding of the links between predictability and market efficiency, in view of the conflicting evidence in prior literature. Practical implications Whilst the pricing process in emerging markets may be hindered by delayed adjustments, in case of established markets it seems that there is a higher tendency for price reversals which could be due to prior over-reactions. Originality/value This study presents evidence of substantial differences in predictability across developed and emerging markets which was gleaned through the rigorous application of different empirical tests.
Keywords: G10; G12; G14; G15; 330; Delayed price adjustments; Emerging markets; Granger-causality; Liquidity; Over-reactions; Predictability; Price discovery; Runs tests; Variance ratio tests; Vector autoregression